Fish species diversity in relation to Physico-chemical water parameters in estuaries and coastal zones of Kuching Bay, Sarawak - Yong, Ai Hua (Universiti Malaysia Sarawak, (UNIMAS), 1999)
The Kuching Bay is one of the most productive fishing ground for Sarawak and accounts for a substantial portion of the total fish landings. This coastal zone is also subjected to increasing industrial, residential, recreational and agricultural development activities. These anthropogenic activities along with natural phenomena have the potential to cause enormous pressure on the ecosystem and thereby exert significant impacts not only on sensitive habitat areas, but also on aquatic communities. This study was carried out as a preliminary initiative to document fish species diversity and physico-chemical water parameters of two predetermined estuaries and coastal sites.